PENERAPAN PEMBERIAN TERAPI MUSIK RELIGI “DEMI MASA” UNTUK PENURUNAN TINGKAT KECEMASAN PASIEN PRE OPERASI DENGAN REGIONAL ANASTESI SUB ARACHNOID BLOK DI RUMAH SAKIT K.R.M.T WONGSONEGORO SEMARANG - Ns. Ainnur Rahmanti; Rani Pratiwi (Jurnal Rumpun Ilmu Kesehatan, 2021)
Anxiety is a normal adaptive response to stress due to surgery. Anxiety caused by fear of pain, fear of physical changes and not functioning normally after surgery, one of the ways to overcome it is with relaxation and distraction techniques, namely with religious music therapy. The purpose of this case study was to describe the application of religious music therapy "Demi Masa" to decrease the anxiety level of preoperative patients with regional sub arachnoid anesthesia blocks in hospitals in the surgical room of RSUD K.R. Wongsonegoro Semarang. This study belongs to descriptive using a case study approach. Subjects in this study were appendicitis patients who would undergo surgery with sub-arachonoid block regional anesthesia, willing to be respondents aged 20-40 years, still cooperative, level of anxiety from mild 14 - 20 to moderate 21-27, like religious music, Muslim. Analysis of anxiety level was carried out descriptively and measured based on anxiety scale without rating scale for anxiety. The results of the analysis showed that there was a decrease in the level of anxiety after the intervention. In subject I moderate anxiety (score 25) became low anxiety (score 15) and low subject II anxiety (score 15) became no anxiety (score 9). In conclusion, this study recommends nurses can apply religious music therapy "Demi Masa" to reduce the patient's anxiety level preoperatively.